Peningkatan Akses dan Peluang Kewirausahaan Mahasiswa melalui Pembelajaran Fotografi Berbasis Proyek Industri di Sistem Pembelajaran Jaringan - Abdul Rahman Prasetyo; Anak Agung Gde Rai Arimbawa; Iriaji; Eka Putri Surya; Alby Aruna; Adinda Marcelliantika; Nila Rahmawati; Ginanjar Atma Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The program to enhance student access and entrepreneurial opportunities through industry-based photography project learning in an online learning system aims to develop students' technical and managerial skills. This program combines theory and practice through real industry-relevant projects, providing a comprehensive and interactive learning experience. Results show significant improvements in students' skills and motivation. With continued support from various parties, this program is expected to sustain improvements in education quality and entrepreneurial opportunities.